A expansão do complexo de soja no Brasil - Contessa, Margareth Anne Camargo (2020)
The subject of this research is to present the expansion of the soy field in Brazil, which was estrategic for the brazilian state too became the leadership of agricultural expansion in the last few years. The purpose is to show that many agrarian political was given as encouragement in the time, mostly in the military government which allowed to have a transmutation of “soybean” in “agribusiness”. We are going to make an analysis of the expansion factors of the product in the international market, realizing the limiting factors in the time of commercialization of them. Understanding that this economic activity will have a bunch of agents, since the fabrication of inputs until the processing, distribution and consumption of these products in natura or industrialized. Constituting a process that began with agronomic research to become a product for internal consumption and/or an exportation commodity. This study approaches the subject of the multiple agents involved in this discussion in a collective or individual way, verifying the force that this activity has to influence the society as a whole, transforming the rural and urban sector.